Accounting for water use and productivity - Molden, David J. (International Irrigation Management Institute, 1997)
This paper presents a conceptual framework for water accounting and provides generic terminologies and procedures to describe the status of water resource use and consequences of water resources related actions. The framework applies to water resource use at three levels of analysis: a use level such as an irrigated field or household, a service level such as an irrigation or water supply system, and a water basin level that may include several uses. Water accounting terminology and performance indicators are developed and presented with examples at all the three levels. Concepts and terminologies presented are developed to be supportive in a number of activities including: identification of opportunities for water savings and increasing water productivity; developing a better understanding of present patterns of water use and impacts of interventions; improving communication among professionals and communication to non-water professionals; and improving the rationale for allocation of water among uses. It is expected that with further application, these water accounting concepts will evolve into a robust, supporting methodology for water basin analysis.